Work-life balance: is it still a new concept in private commercial banking sector of Bangladesh? - Newaz, Mohammad Tanvi; Zaman, Kanij Fatama (© 2012 Consortia Academia Publishing, 2016)
This article was published in International Journal of Research Studies in Management [© 2012 Consortia Academia Publishing] and the definite version is available at : http://www.consortiacademia.org/index.php/ijrsm/article/view/95/108 The journal website is at: http://www.consortiacademia.org/index.php/ijrsm This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Philippines License